Action-création: l’art de performance amérindien au Québec - Beaupré, Jonathan Lamy (Itinéraires, 2015)
Native artists of Quebec working in performance art set up actions that are similar to contemporary forms of rituals. These works have sometimes a poetic or “shamanic” character, are sometimes disturbing, especially through the critique of the clichés about First Nations, or mix those two components. They committed the body of the artist and the audience, while making the Native American cultural expression a both artistic and identity performance
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé